Role of the blue light receptor gene Icwc-1 in mycelium growth and fruiting body formation of Isaria cicadae - Song, Linhao; Shrivastava, Neeraj; Gai, Yunpeng; Li, Dong; Cai, Weiming; Shen, Yingyue; Lin, Fu-Cheng; Liu, Jingyu; Wang, Hongkai (Frontiers in Microbiology, 2023)
It is well known that Isaria cicadae is a highly valued medicinal mushroom because of its economic value and therapeutic use. There is a great demand in food and medical industries as a result natural sources of wild I. cicadae are continuously over-exploited and declining. Consequently, commercial cultivation in a controlled environment is the best way to meet consumer demands. Light is a major factor affecting the growth and development of this precious mushroom at all stages of its life cycle. We identified a blue light receptor white collar-1 (Icwc-1) gene homologue with defined functions in morphological development in I.cicadae. Analysis of its protein sequence revealed that the IcWC-1 protein comprises LOV and PAS domains and a GATA-type zinc finger domain. Using gene knockout technology, mutant of Icwc-1 gene knockout was found to have a significant effect on mycelial growth and synnematal development. In parallel, the blue light receptor gene Icwc-1 is an upstream regulatory gene that can regulate genes related to fruiting body formation, pigment formation genes, and related genes for enzyme synthesis. The above findings will not only provide an important reference for the in-depth study of the physiological mechanism of light regulation in I. cicadae, but also provide new insights for future breeding program and improving this functional food production.